2011
DOI: 10.1051/0004-6361/201116750
|View full text |Cite
|
Sign up to set email alerts
|

Damped large amplitude transverse oscillations in an EUV solar prominence, triggered by large-scale transient coronal waves

Abstract: Aims. We investigate two successive trains of large amplitude transverse oscillations in an arched EUV prominence, observed with SoHO/EIT on the north-east solar limb on 30 July 2005. The oscillatory trains are triggered by two large scale coronal waves, associated with an X-class and a C-class flare occurring in the same remote active region. Methods. The oscillations are tracked within rectangular slits parallel to the solar limb at different heights, which are taken to move with the apparent height profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 48 publications
4
87
0
Order By: Relevance
“…1c), at positions X BOX = 48, 72, 96 arcsec, and Y BOX = 96, 120 arcsec, in a similar way as in previous works (e.g. Hershaw et al 2011;Verwichte et al 2004;). We calculated a mean value over the width at every position along the slit to increase the signal-to-noise ratio.…”
Section: Analysis and Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…1c), at positions X BOX = 48, 72, 96 arcsec, and Y BOX = 96, 120 arcsec, in a similar way as in previous works (e.g. Hershaw et al 2011;Verwichte et al 2004;). We calculated a mean value over the width at every position along the slit to increase the signal-to-noise ratio.…”
Section: Analysis and Resultssupporting
confidence: 56%
“…Typical periods of kink oscillations range from a few minutes to several hours (e.g. Verwichte et al 2010) (the latter case corresponds to cool fibrils of quiescent prominences, Hershaw et al 2011). In terms of magnetohydrodynamic (MHD) wave theory kink oscillations are interpreted as kink (m = 1) fast magnetoacoustic modes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that this could be explained in terms of a tilted wavefront (Warmuth et al, 2004b), where higher parts of the front reach the filament earlier than the lower parts that generate stronger signatures. Filament oscillations have also been detected in He i (Gilbert et al, 2008, see Figure 32) and in EUV, where transverse oscillations are observed (Hershaw et al, 2011;Asai et al, 2012;Gosain and Foullon, 2012). The latter studies showed that the transverse oscillations are caused by the impact of a fast coronal wave.…”
Section: Excitation Of Oscillationsmentioning
confidence: 84%
“…Other phenomena trigerred by EUV waves are kink-like oscillations of disk filaments (Hershaw et al, 2011) and coronal loops (e.g., Wills-Davey and Aschwanden and Schrijver, 2011). The velocity of these transverse oscillations is in the range of 5-50 km s −1 , the same range as filament oscillations trigerred by Moreton waves (e.g., Gilbert et al, 2008); for a review on filamenent/prominence oscillations and their dissipation mechanisms the interested reader can refer to Arregui and Ballester (2011).…”
Section: Kinematics Amplitudes and Dispersionmentioning
confidence: 98%